Strategies for Effective Knowledge Sharing and Encouraging Use of Digital Asset Mapping Platforms: Insights from Community-Based Organizations - Erezi Ogbo-Gebhardt (International Telecommunications Society (ITS), 2024)
Perhaps due to the growing array of digital inclusion programs that are increasingly offered by community organizations, states are examining ways to help their residents search – and determine their eligibility – for programs within their communities. To this end, several states are conducting digital asset mapping and plan to build a publicly accessible repository of these assets. However, there is a risk that the platform will be built yet acceptance and use will be low. This paper discusses the case of North Carolina and presents emergent themes from local community-based organizations on current knowledge sharing practices in digital inclusion ecosystems within communities and insights on key factors to encourage adoption and use of the digital asset inventory platform.
Keywords: 330; Community Informatics; Digital Inclusion; Asset Mapping; Participatory Research; Knowledge Sharing